Functional Properties of Fish Proteins : A Review - T.V., Sankar (Fishery Technology, 2025)
Proteins possess a number of physiochemical characteristics which facilitates their varied food applications. Proteins exhibit a wide range of functionality and versatility during processing. Functional properties of proteins are mainly due to its interaction with other components within the food system. The structure of protein is highly dependent upon the environment and protein assumes different conformations depending upon the conditions of exposure. The surface hydrophobicity plays a major role in the functional properties of a protein and changes in the inherent characteristics influence protein structure which have profound influence on the functional properties of the protein.